Azzi in Between - A Bilingual Experience in the Primary EFL Classroom - Grit Bergner (CLELEjournal, 2016)
The book Azzi in Between (Garland, 2012) provides the opportunity for presenting information on and encouraging understanding of the life of refugees and asylum seekers in the EFL classroom, despite being a challenging picturebook in linguistic terms for young foreign language learners. This paper describes how the content of the book was made accessible to a group of children aged 8 and 9 in Germany through a series of activities which relied upon the support of the classroom teacher to prepare and consolidate activities, thus using both English and German to help children understand and discuss the issues of refugee and asylum seekers.